PELUANG ABRIBISNIS PADA PJPT II - Ibrahim, Jabal Tarik (Jurnal Bestari, 1993)
To solve the problems existing, the way of thinking on agriculture sector has to apply agribusiness approach. It is a system which consists of several subsystems, and one of the maincomponents is farming. The farming has interrelated to the subsystem of industry. As a result, farming is as the central core of agribusiness containing farmers, breeders, and fishermen. They act as the prime producer in agribusiness.